2010
DOI: 10.1111/j.1365-2664.2010.01862.x
|View full text |Cite
|
Sign up to set email alerts
|

Convergence and divergence in plant community trajectories as a framework for monitoring wetland restoration progress

Abstract: Summary1. Environmental policies that use ecological restoration to offset the destruction of natural ecosystems assume that restorations readily compensate for the losses because they progress reliably and predictably over time, following deterministic successional trajectories. However, succession and restoration are spatially and historically contingent processes, often characterized by divergent trajectories that deviate from expectations. 2. We develop a framework for monitoring restorations that integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
146
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(154 citation statements)
references
References 58 publications
(117 reference statements)
2
146
1
Order By: Relevance
“…596 N Invasive Plant Science and Management 7, October-December 2014 restoration actions may be short-lived (Matthews and Spyreas 2010;Rinella et al 2012;Seabloom 2011). By the third year, there were minimal effects of treatment on bare ground and exotic grasses, which raises the question of whether expensive exotic control techniques are justified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…596 N Invasive Plant Science and Management 7, October-December 2014 restoration actions may be short-lived (Matthews and Spyreas 2010;Rinella et al 2012;Seabloom 2011). By the third year, there were minimal effects of treatment on bare ground and exotic grasses, which raises the question of whether expensive exotic control techniques are justified.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have suggested that interannual climatic variation, which is beyond the control of practitioners, may be more important than the restoration method used (Cox and Allen 2011;Wilson et al 2004), so that investing resources in multiple years of seeding or planting may enhance restoration success more than expensive efforts to control exotic competition. What is clear is that long-term monitoring is needed to evaluate the efficacy of different restoration treatments, a call that has been made repeatedly in the academic literature (Matthews and Spyreas 2010;Rinella et al 2012), but is less commonly implemented (Kettenring and Adams 2011). Clearly, selecting among the options of no treatment, mulching, herbicide, and tarping will require balancing long-term efficacy with costs and logistical constraints at specific sites, as well as considering the effect of the treatments on any extant native vegetation and seed bank.…”
Section: Resultsmentioning
confidence: 99%
“…The typical approach used is through comparisons of the restored sites with undisturbed reference systems and degraded systems (Matthews and Spyreas, 2010;Rey Benayas et al, 2009). However, most studies taking this approach have focused on plants, largely disregarding faunal recovery (Brudvig, 2011;Majer, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of restoration progress is a critical step in the application and refinement of restoration strategies, enabling the identification of constraints to success and the prediction of restoration outcomes (Matthews and Spyreas, 2010). The typical approach used is through comparisons of the restored sites with undisturbed reference systems and degraded systems (Matthews and Spyreas, 2010;Rey Benayas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, most mitigation performance criteria include the establishment of a desirable wetland plant community, commonly measured in a transect-or quadrat-based estimate of percent cover and a measure of floristic quality like the coefficient of conservatism (Matthews & Endress 2008). The desirable plant community can be facilitated, to some degree, by manipulation of the hydrologic regime (Zedler 2000;Simenstad et al 2006), by amendment of substrate and seed bank (Brown & Bedford 1997), and by introduction of certain plant species and management of undesirable species (Matthews & Endress 2008;Matthews & Spyreas 2010). A potential trade-off in this quest for the desirable plant community is the loss of heterogeneity; indeed, establishment and maintenance of a particular plant community can mean regularization of the disturbance regime and minimization of natural recruitment (Zedler 2000;Brooks et al 2005).…”
Section: Introductionmentioning
confidence: 99%